Proceedings of The 7th Indonesia Japan Joint Scientific Symposium, The 24th Ceres International Symposium, The 4th Symposium on Microsatellite for Remote Sensing (SOMIRES 2016), The 1st Symposium - Elyas Palentei, Katsumi Hattori,dkk (Chiba University, 2016)
Proceedings of The 7th Indonesia Japan Joint Scientific Symposium, The 24th Ceres International Symposium, The 4th Symposium on Microsatellite for Remote Sensing (SOMIRES 2016), The 1st Symposium on Innovative Microwave Remote Sensing